Molecular radiotherapy using cleavable radioimmunoconjugates that target eGFR and γH2AX - Cornelissen, B; Waller, A; Able, S; Vallis, K; Vallis, K (2013)
Many anticancer therapies, including ionizing radiation (IR), cause cytotoxicity through generation ofDNA double-strand breaks (DSB). Delivery of therapeutic radionuclides to DNA DSB sites can amplify this DNA damage, for additional therapeutic gain. Herein,wereport on two radiopharmaceuticals, radiolabeled with the Auger electron emitter 111In, with dual specificity for both the intranuclear, DNA damage repair signaling protein γH2AX and the EGF receptor (EGFR). The EGFR ligand EGF was conjugated to a fluorophore- or 111In-labeled anti-γH2AX antibody, linked via a nuclear localization sequence (NLS) to ensure nuclear translocation. EGF conjugation was achieved either through a noncleavable PEG linker (PEO6) or a cleavable disulfide bond. Both conjugates selectively bound EGFR on fixed cells and γH2AX in cell extracts. Both compounds enter EGFR-expressing cells in an EGF/EGFR-dependent manner. However, only the cleavable compound was seen to associate with γH2AX foci in the nuclei of irradiated cells. Intracellular retention of the cleavable compound was prolonged in γH2AX-expressing cells. Clonogenic survival was significantly reduced when cells were exposed to IR (to induce γH2AX) plus 111In-labeled cleavable compound compared to either alone and compared to nonspecific controls. In vivo, uptake of 111In-labeled cleavable compound in MDA-MB-468 xenografts in athymic mice was 2.57 ± 0.47 percent injected dose/g (%ID/Υ) but increased significantly to 6.30 ± 1.47%ID/g in xenografts where γH2AX was induced by IR (P < 0.01). This uptake was dependent on EGF/EGFR and anti-γH2AX/γH2AX interactions. We conclude that tumor-specific delivery of radiolabeled antibodies directed against intranuclear epitopes is possible using cleavable antibody-peptide conjugates. Mol Cancer Ther; 12(11); 2472-82. © 2013 AACR.